PEMBELAJARAN VISUALIZATION, AUDITORY, KINESTHETIC (VAK): BAGAIMANA GURU MENGEMBANGKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SEKOLAH DASAR - Annisa Nurfitriani; Ihsan Rizali; Asep Nurhuda; Atep Lesmana; Hany Handayani; Gemi Gustiani; Putri Oktaviani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2023)
Mathematical communication ability is one of the important competencies that must be developed in every math topic, because mathematical communication can help students in building mathematical knowledge. However, the facts in the field, students' mathematical communication skills are still low. The purpose of this study was to determine the effect of the Visualization, Auditory, and Kinesthetic (VAK) learning model on the mathematical communication skills of fourth grade students at SDN Maracang on the circumference and area of ​​flat shapes. The method used in this study is a quasi-experimental method with a research design Nonequivalent (Pretest-Posttest) Control Group Design. The population in this study were fourth grade students at SDN Maracang and the samples taken were grades IV B and IV D with 24 students each. Samples were taken using purposive sampling technique with certain considerations. Data collection techniques used are tests and questionnaires. Data analysis in this study used the t-test of N-gain data which was preceded by normality and homogeneity tests. The results of the study obtained a significance value of 0.000 <0.05, meaning that there was an effect of the VAK learning model on students' mathematical communication skills. From the results of the N-gain test, it was found that there was an increase in mathematical communication skills with the average N-gain of the experimental class was 0.4921 in the medium category and the control class average was 0.0404 with the low category. Based on these results, it can be concluded that the use of the VAK learning model has more influence on mathematical communication skills than the use of conventional learning models.